Analysis of the Utilization of Online Mandatory Corporate Employment Report Platform in Compliance With the Implementation of Employment Norms in South Sulawesi Province - Amin, Rizal; Ibrahim, Muh Akmal (KnE Social Sciences, 2025)
The mandatory employment report platform (WLKP) is one of the digital innovations in employment supervision developed by the Ministry of Manpower of the Republic of Indonesia. The corporate employment reporting mandatory platform has been used in Indonesia since 2017 to increase transparency in monitoring the company’s compliance with labor norms. This study aims to analyze the use of the online Mandatory Corporate Employment Reporting Platform (WLKP) in South Sulawesi Province in the hope of providing input related to better employment governance policies in the future. The research method used is mixed methods (descriptive-qualitative and quantitative). The total company population in this study is 40.867 companies and 27 informants (10 labour inspectors, 16 company administrators, and 1 WLKP admin). The results of the study show that the percentage of compliance with companies related to WLKP online in South Sulawesi Province for 2022 is 2.8%, in 2023 as much as 9.45%, in 2024 as much as 10.2%, and at the end of April 2025 as much as 14.43%. Of course, this achievement is still categorized as very low in its utilization. The online WLKP platform has helped in making it easier for labor supervisors to conduct inspections; however, there are still obstacles experienced by companies in terms of socialization, data accuracy, company responsiveness, digital infrastructure, and system integration. The recommendations given include increasing capacity for users, especially labor inspectors and the Company in the form of WLKP technical guidance, adding features and integration with a wider system, and enforcing legal sanctions for employers who have not complied.